EVALUASI KEBIJAKAN TATA NASKAH DINAS DI UNIVERSITAS LANCANG KUNING - sari, ermina; dailiati, surya; saputra, trio (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
This study aims to examine the official script in the environment of universitas lancang kuning, making the manuscript format of the paper work aliralur script of the service as needed, this study was lifted from the existing phenomenon in the universitas lancang kuning that has no provision in making the official script, this study using the method qualitative descriptive research, which is available or builds a unity or explains the meaning behind reality. Researchers are based on the reality or ongoing events in the field. Furthermore, researchers will explore further phenomena that occur. The results show that the implementation of the official script has not been effective because the regulations on the official script of the universitas lancang kuning environment has no legal umbrella. a recommendation that would be taken into consideration in the improvement of grammar is that the university should immediately issue a policy on the legal document. In order for performance in each unit can be increased and avoided from overlapping authority. As well as candy and research about the official script can be a reference in the regulation of yellow university environment, because simply in the provisions have been described the official script of the manufacture of symbols, heads of departments, examples of making official script, stamp and format disposition sheet.